Pengaruh Return On Asset (ROA) terhadap Return Saham Syariah dengan Struktur Modal Sebagai Variabel Moderasi pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Indeks Saham Syariah Indonesia Periode 2015-2019 - Asti Endang; Martha Ayerza Esra (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
Abstract Along with the development of the Islamic financial system, the capital market has developed into a sharia capital market which is here to offer an attractive alternative compared to the conventional industry which still relies on usury as its basic foundation throughout 2019, Islamic stocks have performed well. At the close of trading at the end of 2019, the Islamic stock index recorded higher growth than the stock price index (JCI). This is thought to have occurred due to strict requirements to become a sharia issuer, which is one of the provisions regarding the company's funding structure. In this study, the authors use theories from experts and there are also other sources to support the variables studied. The theory used is the signal theory, the theory of profitability, capital structure, stock returns. As well as previous research regarding the relationship of Return On Assets (ROA) with stock returns and the relationship between capital structure and stock returns which are the moderator variables in this study. The object of this research is the various industrial sector manufacturing companies registered at ISSI. Data collection techniques using secondary data in the form of stock price information and the company's annual financial statements. The sampling technique is a non-probably sampling technique with purposive sampling method with criteria that have been determined by the author. Data analysis technique to test this research is Moderated Regression Analysis (MRA) with SPSS application. The object of research is all companies listed in the Indonesian sharia stock index in the various industries sector in 2015-2019. The results showed (1) Return on Assets (ROA) had no effect on Islamic stock returns. (2) The capital structure is not able to moderate or strengthen the relationship between ROA and Islamic stock returns.